Maximizing diver score by examining discrepancies in diver competency and judges` marks - McGee, M. (Journal of Sports Analytics, 2025)
Central to diving competitions is the diver's "dive list", which is the list of dives an athlete will perform during a competition. Coaches and divers work together to balance dive list difficulty so that a diver remains competitive without exceeding his or her capabilities. In this work, we examine the discrepancy between a diver's ability and judges` scores in springboard diving meets with the purpose of discovering biases in scoring that might allow a diver to complete an advantageous dive list. A diver's ability, called the competency score, is estimated by the mean score for all dives and all meets in which the diver has participated. We use the term "discrepancy" to indicate the difference between a judge's score in each meet and the diver's competency score; therefore, discrepancy reflects the gap between the judges` assessment of a diver's performance and his or her actual ability. The notions of competency and discrepancy are applied to a data set for high-school one meter diving competitions in the US from 2017 to 2022. Using visualizations and a mixed-effects model, we show that a large part of discrepancy in scores can be explained by the position, direction, and difficulty of the dive.